Genome‐Wide CRISPR/Cas9 Library Screening Revealed Dietary Restriction of Glutamine in Combination with Inhibition of Pyruvate Metabolism as Effective Liver Cancer Treatment. Issue 34 (30th October 2022) - Yang, Chunxue; Lee, Derek; Zhang, Misty Shuo; Tse, Aki Pui‐Wah; Wei, Lai; Bao, Macus Hao‐Ran; Wong, Bowie Po‐Yee; Chan, Cerise Yuen‐Ki; Yuen, Vincent Wai‐Hin; Chen, Yiling; Wong, Carmen Chak‐Lui
Abstract: Hepatocellular carcinoma (HCC) is the second most lethal cancer worldwide. Glutamine is an essential, extracellular nutrient which supports HCC growth. Dietary glutamine deficiency may be a potential therapeutic approach for HCC. HCC cells overcome metabolic challenges by rewiring their metabolic pathways for rapid adaptations. The efficiency of dietary glutamine deficiency as HCC treatment is examined and the adaptation machinery under glutamine depletion in HCC cells is unraveled. Using genome‐wide CRISPR/Cas9 knockout library screening, this study identifies that pyruvate dehydrogenase α (PDHA), pyruvate dehydrogenase β (PDHB), and pyruvate carboxylase (PC) in pyruvate metabolism are crucial to the adaptation of glutamine depletion in HCC cells. Knockout of either PDHA, PDHB or PC induced metabolic reprogramming of the tricarboxylic acid (TCA) cycle, disrupts mitochondrial function, leading to the suppression of HCC cell proliferation under glutamine depletion. Surprisingly, dietary glutamine restriction improves therapeutic responses of HCC to PDH or PC inhibitor in mouse HCC models. Stable isotope carbon tracing confirms that PDH or PC inhibitors further disrupt the metabolic rewiring of the TCA cycle induced by dietary glutamine depletion in HCC. In summary, the results demonstrate that pyruvate metabolism acts as novel targetable metabolic vulnerabilities for HCC treatment in combination with a glutamine‐deficient diet. Abstract : Herein, the authors identify and functionally characterize pyruvate metabolism as metabolic vulnerabilities for HCC treatment using genome wide CRISPR library screening. Suppressing either pyruvate dehydrogenase (PDH) or pyruvate carboxylase (PC) in pyruvate metabolism leading to metabolic disruption of TCA cycle and sensitizing tumors to the treatment of glutamine dietary restriction.